(5x - 3) / 6 - (x + 3) / 6
= [ (5x - 3) - (x + 3) ] / 6
= [ 5x - 3 - x - 3 ] / 6
= [ 5x - x - 3 - 3 ] / 6
= [ (5 - 1)x - (3 + 3) ] / 6
= (4x - 6) / 6
= 2(2x - 3) / 6
= (2x - 3) / 3
= (2x / 3) - 1.
The last two lines are both acceptable forms for a final answer.
2007-05-16 01:12:30
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
a million. x/12+3x/12 = 4x/12 = x/3 2. 5x-3 /6 -x+3 / 6 is that (5x-3)/6 - (x+3)/6 = (4x-6)/6 = (2x-3)/3 = 2/3 x -a million or 5x -0.5 -x +0.5 ? = 4x it is without brackets (yet we've all extra them for you it form of feels) KIS save it elementary
2016-12-11 10:58:02
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
(5x-3)/6 - (x+3)/6
Since they have the same denominator, you can combine them
((5x-3) - (x+3))/6 =
(5x - 3 - x - 3)/6 =
(4x - 6)/6 =
4x/6 - 6/6 =
2x/3 - 1 ===> final answer
2007-05-16 01:10:40
·
answer #3
·
answered by detektibgapo 5
·
0⤊
0⤋
(5x-3)/6 - (x+3)/6
This actually isn't an equation since there is no equal(=) sign.
If you mean:
(5x-3)/6 = (x+3)/6 [multiply x 6]
(5x-3) = (x+3) [Add 3 to each side]
5x = x + 6 [Subtract x from each side]
4x = 6 [Divide both sides by 4]
x = 6/4 = 1.5
If your original was correct:
(5x-3)/6 - (x+3)/6
(5x-3)/6 +(-x-3)/6
(4x-6)/6
(2x-3)/3
2007-05-16 01:33:03
·
answer #4
·
answered by anerasescovedo 4
·
0⤊
0⤋
x=0
2007-05-16 01:07:47
·
answer #5
·
answered by Anonymous
·
0⤊
2⤋
[(5x - 3) - (x + 3)]/6 = (5x - 3 - x - 3)/6 = (4x - 6)/6 = 4x/6 - 6/6 =
= 2x/3 - 1
2007-05-16 01:08:55
·
answer #6
·
answered by Amit Y 5
·
2⤊
0⤋
I would think the solution is to combine these two sets into one fraction
(5x-3)-(x+3)
----------------
6
Then add like terms in the numerator
5x-x-3-3
-----------
6
4x-6
------
6
2x-3
------
3
It could further be simplified in this way
2
--x - 1
3
2007-05-16 01:15:28
·
answer #7
·
answered by shanusav 2
·
0⤊
0⤋
24x
Mutiply by 6 to clear the fraction.
(30x - 18) - (6x +18)
Do the math
2007-05-16 01:11:49
·
answer #8
·
answered by Ronnie M 1
·
0⤊
0⤋
a) (5x-3)/6 - (x+3)/6
b) ( (5x-3) - (x+3) )/6
c) ( 5x-3-x-3)/6
d) (4x - 6) / 6
e) (4x/6) - (6/6)
f) (2x/3) - 1
2007-05-16 01:11:44
·
answer #9
·
answered by findandreplace 3
·
0⤊
0⤋
ok
(5x-3/6)=(x+3)/6 assuming whole equation = 0
mulitply though by 6
5x-3=x+3
4x=6
x=1.5
2007-05-16 01:06:31
·
answer #10
·
answered by colesey72 4
·
0⤊
2⤋